Thermodynamic Kinetic Parameters of Some Transition Metal Complexes of Schiff Base
Complexes of Cu(II), Ni(II), Co(II), Fe(IlI) and Mn(II) with Schiff base are prepared by condensation of 3-acety-6-methyl-(2H